THE DETERIORATION OF HERO IN WILLIAM SHAKESPEARE’S OTHELLO THE MOOR OF VENICE. - Sapa, Gregorius; Doi, Maksimilianus; Wanggai, Febe F I (Fakultas Hukum dan Sosial Humaniora Universitas Flores, 2022)
This study aimed at describing Othello’s deterioration in William Shakespeare’s The Moor of Venice through the intrinsic aspects of the drama. This study adopted structuralism approach and the theory of wholeness to answer the problem issued. This study used descriptive qualitative design that the data were taken from William Shakespeare the Tragedy of Othello the Moor of Venice edited by Alvin Kernan (1963). The results denote that Othello has flaws which lead to his deterioration. Gullible and excessive in loving his wife are the flaws that produce jealousy. Finally, without knowing the fact, Othello kills his wife, and he also kills himself after realizing the truth. The flaws of Othello are identified through plot, character, thought/theme, diction, rhythm, and spectacle.